Airport Management System: Core Transaction 2 (Iata et al./Iata Bag Tag Printing, Departure Control, Arrival Control, Interactive Seat Maps, Immigration): Vol. 5, No. 1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The airport management system plays a vital role in the transportation sector, particularly in core transactions, by facilitating the transportation processes of passengers to the destination they want to be. The Airport management system: CORE TRANSACTION 2 is a comprehensive solution that provides the needs of external clients/passengers regarding their transactions outside Skystream Enterprise Company. The CORE TRANSACTION 2 project focuses on the needs and validates the transaction that has been placed when the clients have a booking in our company. The existing Airport management system often lacks efficiency and productivity in managing real-time operations, resulting in transaction delays, inefficient services, and, lastly, loss of profit for the company.The project team uses agile methodology. The project team collects the data through online interviews, observations, and collaboration with the stakeholders to identify the key features that must be provided during the development of the system. By incorporating the stakeholders’ feedback, the project team will continue to promote improvements and focus to the key features in the development of Airport management system: Core transaction 2.The Airport management: Core transaction 2 provided positive outcomes for stakeholders in the Airlines industry, with its efficient kiosk features that provides productivity to the airlines, reduces delayed transactions and enhance passenger satisfaction, resulting to the company's productivity and efficient services to the passengers.The implementation of the Airport Management system, Core Transaction II, has had significant benefits in the airline industry. By using an agile and goal-driver approach, the project team provides efficient and productive projects in the airline industry. The project team promoted beneficial changes in the airline industry by promoting new features, such as the kiosk feature, which creates an opportunity for the airline industry to promote security, efficiency, and productivity. The Airport management system: Core Transaction II will expect further improvements in the future by implementing new features that will make the project more efficient than the previous implementations, and those features will be the key to the success of the project in terms of functionality, efficiency, and productivity.
Keywords: Core Transaction 2